2020
DOI: 10.1016/j.istruc.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Punching of RC slabs without transverse reinforcement supported on elongated columns

Abstract: The paper investigates the influence of support elongation on punching resistance at internal slab column connections without shear reinforcement. Nonlinear finite element analysis (NLFEA) with 3-D solid elements is used to study the influence of column elongation on stress and strain in the slab around the column. Punching failure is shown to be triggered by localised peaks in shear stress around the corners of the support. Significantly, one-way shear is shown to increase the shear resistance of slabs suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…This zero-stress region is assumed to denote the end of the region where two-way shear has a significant impact on the slab behavior. The influence of two-way shear being confined to a small region near the end of an elongated column or wall has also been suggested by Setiawan et al 14,19 In their model used to predict the punching capacity of slab-column and slab-wall connections the region influenced by two-way shear is assumed to have a length of 1.5d to match that assumed in Model Code 2010. 28 Additionally, their model includes a 1.5d long region between the two-way and one-way shear regions which is assumed to be under very low stress.…”
Section: Study-concentric Loading Study Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…This zero-stress region is assumed to denote the end of the region where two-way shear has a significant impact on the slab behavior. The influence of two-way shear being confined to a small region near the end of an elongated column or wall has also been suggested by Setiawan et al 14,19 In their model used to predict the punching capacity of slab-column and slab-wall connections the region influenced by two-way shear is assumed to have a length of 1.5d to match that assumed in Model Code 2010. 28 Additionally, their model includes a 1.5d long region between the two-way and one-way shear regions which is assumed to be under very low stress.…”
Section: Study-concentric Loading Study Resultsmentioning
confidence: 90%
“…Therefore, the one‐way shear region is assumed to start at a distance of 3d from the end of the support, which is smaller than the length of 5d suggested by the ABAQUS results presented herein. However, it should be noted that the model proposed by Setiawan et al 14,19,35 is based on the shear stresses along the critical perimeter located at d /2 from the column/wall face and not the column/wall perimeter.…”
Section: Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to laboratory test data, the JSPME is validated using virtual slab-column specimens simulated with NLFEA using 3D solid elements. The solid element analysis was carried out with ATENA [8] using the procedure of Setiawan et al [6,9,10] who in [6] analysed punching failure of 16 slabs without shear reinforcement having either square supports (14) or elongated supports (3). The resulting mean value of Ptest/Ppredicted was 0.95 with a coefficient of variation of 7.3%.…”
Section: Nonlinear Finite Element Analysis With 3d Solid Elementsmentioning
confidence: 99%
“…The punching shear failure sparks a vital interest in the community of engineers, designers, and scientists to be taken into consideration, as the subject of different investigations to describe their complex mechanism of punching shear failure and behavior of slab–column connections. Scientific research (e.g., [ 19 , 20 ]) has indicated that for large or elongated supports the shear force distribution near the support is uneven despite symmetrical loading ( Figure 2 ). In the case of internal columns loaded symmetrically, the unevenness of the shear forces may also be caused by the geometry of the floor slab [ 21 , 22 ] or the distribution of longitudinal reinforcement [ 23 ].…”
Section: Introductionmentioning
confidence: 99%